2022
DOI: 10.1177/03635465211068532
|View full text |Cite
|
Sign up to set email alerts
|

Why, When, and in Which Patients Nonoperative Treatment of Anterior Cruciate Ligament Injury Fails: An Exploratory Analysis of the COMPARE Trial

Abstract: Background: The optimal treatment strategy for patients with an anterior cruciate ligament (ACL) rupture is still under debate. Different determinants of the need for a reconstruction have not been thoroughly investigated before. Purpose: To investigate why, when, and which patients with an ACL rupture who initially started with rehabilitation therapy required reconstructive surgery. Study Design: Case-control study; Level of evidence, 3. Methods: In the Conservative versus Operative Methods for Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In the other study, most patients who had unsuccessful rehabilitation therapy after ACL injury reported instability, not optimal knee function, and pain during activity. They required and underwent a delayed ACL reconstruction [13]. Increased vascularity and remodeling of human ACL graft in the first year after surgery indicate its insufficient mechanical properties, and need for an extended rehabilitation program [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the other study, most patients who had unsuccessful rehabilitation therapy after ACL injury reported instability, not optimal knee function, and pain during activity. They required and underwent a delayed ACL reconstruction [13]. Increased vascularity and remodeling of human ACL graft in the first year after surgery indicate its insufficient mechanical properties, and need for an extended rehabilitation program [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, an even more contentious issue is the potential to mitigate joint degradation by ACL reconstruction, as there are conflicting findings regarding the optimal strategy for preventing knee OA [ 4 , 26 , 31 , 32 , 42 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior cruciate ligament reconstruction (ACLR) is an effective method to restore knee joint function and reduce the risk of joint degeneration [ 2 , 3 ]. Especially for adolescents and people engaged in physical work, surgical treatment is the cost-effective option [ 4 , 5 ]. Many factors can influence the prognosis of ACLR, such as type of graft, surgical technique, rehabilitation protocol, etc.…”
Section: Introductionmentioning
confidence: 99%